WATERTIGHT AND STIFF MOTOR SUSPENSION - WOLF, Harold; SCHALLIG, Michiel, Allan, Aurelius; ZIJLSTRA, Marcel, Hilco; ROETERT, Rob; EIJKELKAMP, Marcus, Franciscus; VAN DEN BERG, René; HAAGSMA, Hendrik, Klaas (2022)
The invention relates to a motor suspension for rigid and watertight mounting of a motor to a housing of an electric device, an electric device comprising such a motor suspension and a hair cutting device comprising an electric device with such a motor suspension. The motor suspension comprises a motor fixation element, a sealing suspension element and a motor axis seal. The motor fixation element is configured to provide a rigid connection of a motor to a housing in one direction, while it provides some flexibility in another direction for not deforming the housing. The sealing suspension element is configured for providing a fluid-tight connection to the housing, and the motor axis seal is configured for providing a fluid tight connection of the sealing suspension element to a rotational axis of the motor.